(untitled) (Polifonia, 2015)
Neste artigo, analisamos o funcionamento discursivo determinante dos efeitos de sentidos que significam concepções de língua(gem) e de sujeito nas formulações constitutivas de uma cartilha produzida para orientar o trabalho pedagógico com aprendizes diagnosticados com necessidades especiais de alguma ordem. Nossas análises recaíram sobre recortes dessa cartilha em que foi possível identificar a estabilização de tais concepções, o que foi feito a partir de considerações iniciais que pontuaram nossa reflexão acerca da questão da inclusão. Entre os resultados decorrentes de nossa análise, destacamos a compreensão de que essa cartilha filia-se a uma formação discursiva fortemente regulada por práticas determinantes do conhecimento produzido no campo das neurociências. PALAVRAS-CHAVE: língua(gem), sujeito, inclusão DISCOURSES ABOUT LANGUAGE AND SUBJECT IN EDUCATIONAL REGULATORY DOCUMENTS: THE ISSUE OF INCLUSION ABSTRACT: In this article, we analyzed the discourse work which determines sense effects that signify language and subject conceptions in constitutive formulations taken from a booklet published to guide the pedagogical practices carried out with learners who have been diagnosed with some sort of special needs. Our analyses were performed upon a few extracts taken from the booklet and allowed us identify certain the stabilization of such conceptions. This procedure was carried out based on a few considerations that outlined our position concerning the issue of educational inclusion. Among the results produced by our analyses, we highlight the understanding that the booklet aligns with a discursive formation strongly regulated by practices that are responsible for the knowledge produced in the field of neuroscience. KEYWORDS: language, subject, inclusion